Sentencing reform in overcrowded times : a comparative perspective - Tonry, Michael H.; Hatlestad, Kathleen (Oxford University Press, 1997)
This volume brings together articles on sentencing reform in the United States, other English-speaking countries (Australia, Canada, England, Wales, New Zealand, South Africa), and Western Europe, by leading national and international authorities. Issues include sentencing policy, practices, and institutions. The articles, by leading experts, are short and readable, and originally appeared in the journal "Overcrowded Times."